2018
DOI: 10.1161/jaha.117.007505
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Adiposity and Lean Mass With Long‐Term Cardiovascular Events in Patients With Coronary Artery Disease: No Paradox

Abstract: BackgroundPrognosis based on body fat percentage (BF%) in patients with coronary artery disease has not been extensively studied. We tested the hypothesis that patients with coronary artery disease and increased BF% have a higher risk for major adverse cardiovascular events (MACEs) and that fat‐free mass is associated with better prognosis.Methods and ResultsWe included 717 patients referred to cardiac rehabilitation after coronary artery disease events or procedures who underwent air displacement plethysmogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 39 publications
(85 reference statements)
2
41
0
3
Order By: Relevance
“…According to the obesity paradox, a higher BMI may be protective against CAD. However, recent findings suggest that this paradox may be a fallacy [15]. Medina-Inojosa et al [15] suggest that the number of major adverse cardiovascular events is greater with increased body fat percentage and decreased lean body mass-not simply with increased BMI-which shows the importance of assessment of fat and lean mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the obesity paradox, a higher BMI may be protective against CAD. However, recent findings suggest that this paradox may be a fallacy [15]. Medina-Inojosa et al [15] suggest that the number of major adverse cardiovascular events is greater with increased body fat percentage and decreased lean body mass-not simply with increased BMI-which shows the importance of assessment of fat and lean mass.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent findings suggest that this paradox may be a fallacy [15]. Medina-Inojosa et al [15] suggest that the number of major adverse cardiovascular events is greater with increased body fat percentage and decreased lean body mass-not simply with increased BMI-which shows the importance of assessment of fat and lean mass. Our results are consistent with their data in that our cohort had greater metabolic abnormalities in the excess fat and obese groups when FMI was used for analysis than with BMI use [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Recently, several studies showed some evidence that body composition, especially lean body mass (muscle) may play an independent role on survival in patients with disease such as cancer and cardiovascular diseases. [34][35][36] Body composition has a potential to provide important prognostic information to improve survival among patients, and thus more studies are warranted to better understand this association in diverse patient populations.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…8 Although this cohort comprised healthy individuals, in those with CVD the obesity paradox disappears when body fat is measured instead of body mass index (BMI). 9 Higher body fat was associated with adverse cardiovascular events, and, on the contrary, higher fat-free mass was associated with a lower risk of events. 9 Recent work by Zaccardi et al 10 aimed to address the inherent issues with reporting hazard ratios by estimating residual life expectancy across fitness and BMI levels.…”
mentioning
confidence: 99%